2006
DOI: 10.1088/0953-4075/39/14/012
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally resolved partial cross sections and asymmetry parameters for carbon K-shell photoionization of the CO2molecule

Abstract: We have measured the vibrationally resolved partial cross sections σ v 1 and asymmetry parameters β v 1 for C K-shell photoionization of the CO 2 molecule in the u shape resonance region above the C K-shell ionization threshold. The positions of both the maxima of σ v 1 and the minima of β v 1 move towards the C K-shell threshold with increasing symmetric stretching vibrational excitation v 1 in the C 1s single-hole state. Calculations employing the relaxed-core Hartree-Fock approach reproduce the observed vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…It is interesting to note that the effective displacement given by Eq. (24) is the same as the one that was obtained earlier in the theory of shape resonances [26][27][28], as a natural consequence of the Taylor expansion.…”
Section: Photoionization Cross Sectionsupporting
confidence: 53%
“…It is interesting to note that the effective displacement given by Eq. (24) is the same as the one that was obtained earlier in the theory of shape resonances [26][27][28], as a natural consequence of the Taylor expansion.…”
Section: Photoionization Cross Sectionsupporting
confidence: 53%
“…High-resolution measurements for core-level photoelectron spectra (PES) of molecules carried out on soft x-ray beamlines at the third generation synchrotron radiation light sources revealed the distribution of the vibrational levels in the core-hole state and the photoelectron angular distribution vary in the shape resonance region. Such studies have been predicted by Dehmer et al [2] and reported for CO [3], H 2 CO [4], N 2 [5], C 2 H 2 [6], CO 2 [7,8] and NO [9].…”
Section: Introductionsupporting
confidence: 70%
“…"#$%!& seem to be similar for N c while they are significantly different for N t . Below we will extract this difference employing the spectral line fitting procedure described elsewhere [4][5][6][7][8][9][10].…”
Section: Theoretical Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of full Herzberg-Teller type vibronic interaction has been discussed [6] in this context, but more typically approaches based upon treating the parametric dependence of the electronic matrix element upon nuclear geometry have provided understanding. Such investigations have mainly addressed the localized K-edge ionization of diatomic [7][8][9][10][11] and triatomic [12,13] molecules in the vicinity of shape resonances. Only very recently have such case studies extended to consider PADs in larger non-linear polyatomics [14] and/or valence shell ionization.…”
Section: Introductionmentioning
confidence: 99%